Three-dimensional inhomogeneity of electron-temperature-gradient turbulence in the edge of tokamak plasmas. (1st August 2022) - Parisi, J.F.; Parra, F.I.; Roach, C.M.; Hardman, M.R.; Schekochihin, A.A.; Abel, I.G.; Aiba, N.; Ball, J.; Barnes, M.; Chapman-Oplopoiou, B.; Dickinson, D.; Dorland, W.; et al.
Abstract: Nonlinear multiscale gyrokinetic simulations of a Joint European Torus edge pedestal are used to show that electron-temperature-gradient (ETG) turbulence has a rich three-dimensional structure, varying strongly according to the local magnetic-field configuration. In the plane normal to the magnetic field, the steep pedestal electron temperature gradient gives rise to anisotropic turbulence with a radial (normal) wavelength much shorter than in the binormal direction. In the parallel direction, the location and parallel extent of the turbulence are determined by the variation in the magnetic drifts and finite-Larmor-radius (FLR) effects. The magnetic drift and FLR topographies have a perpendicular-wavelength dependence, which permits turbulence intensity maxima near the flux-surface top and bottom at longer binormal scales, but constrains turbulence to the outboard midplane at shorter electron-gyroradius binormal scales. Our simulations show that long-wavelength ETG turbulence does not transport heat efficiently, and significantly decreases overall ETG transport—in our case by ∼40%—through multiscale interactions.